Benchmarking Australian enabling programmes: assuring quality, comparability and transparency. Issue 4 (19th May 2021) - Syme, Suzi; Davis, Charmaine; Cook, Chris
Abstract: Cross institutional benchmarking provides the opportunity to ensure comparability of standards by comparing learning outcomes and assessment practices, and acts as a catalyst for change and improved practice. The comparability of standards is crucial for the transparency and portability of qualifications as well as the assurance of quality student learning outcomes. In Australia there are 48 enabling programmes which provide non-award preparatory study for students who would otherwise be excluded from higher education. Given the diversity of programmes and offerings, this pilot study investigated whether it was possible to establish common learning outcomes and standards across three regional Australian enabling programmes that could set the stage for a national benchmarking framework. Three Australian enabling programmes benchmarked their learning outcomes, curriculum and assessment practices in three subjects: study skills preparation, academic communication and mathematics. The findings clearly indicated that despite differences in offerings and programme structure, there were common learning outcomes and standards, the assessments and assessment practices were comparable and rigorous, and that best practice could be shared and adapted to the benefit of students, staff and institutions.